2008
DOI: 10.1002/sec.28
|View full text |Cite
|
Sign up to set email alerts
|

Mobile anonymity of dynamic groups in vehicular networks

Abstract: Vehicular networks are an emerging network to improve safety, efficiency, and convenience of the existing transportation system. In order to preserve privacy in vehicular networks, it is desirable to keep users anonymous. In this paper, we argue that existing approaches, for example, ring singature and anonymous authentication, are susceptible to intersection attack in vehicular networks, resulting in reduced anonymity, even no anonymity. To quantify the achievable anonymity, we first define a graph-based mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…To achieve the privacy ring signature scheme is proposed in [10] and [11]. This scheme provides unconditional privacy and removes the need of group manager.…”
Section: Proposed Schemementioning
confidence: 99%
“…To achieve the privacy ring signature scheme is proposed in [10] and [11]. This scheme provides unconditional privacy and removes the need of group manager.…”
Section: Proposed Schemementioning
confidence: 99%
“…Many studies have been reported on the security and privacy-preservation issues for VANETs [10], [11], [12], [13], [14], [15], [16], [17], [18], [8], [9]. Xi et al [8], [9] introduced a random key-set-based authentication protocol to preserve the vehicle's privacy. However, they only provide the unconditional anonymity without an effective and efficient tracking mechanism.…”
Section: B Related Workmentioning
confidence: 99%
“…To address these issues, this paper proposes an efficient and spontaneous conditional privacy preservation protocol for intervehicle communication based on revocable ring signature [34]. Compared to previous message-authentication schemes [10], [11], [12], [13], [14], [15], [16], [17], [18], [8], [9], our scheme has the following unparalleled features: (1) Conditional privacy: Using the revocable ring signature to secure the intervehicle communication, enables preserving privacy regarding user identity and location of the vehicle, and the identities of the target vehicles can be only revealed by the trusted authority; (2) Efficiency: The proposed protocol can efficiently deal with a growing revocation list instead of relying on a large storage space at each vehicle or updating the group public key and private key at all unrevoked vehicles; (3) Spontaneity: The proposed protocol does not employ RSUs to assist vehicles in authenticating messages while providing fast message authentication and verification and an efficient conditional privacy tracking mechanism. We believe this protocol is an excellent candidate for the future VANETs.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, an adversary can either forge bogus messages to mislead other drivers or track the locations of the intended vehicles. Therefore, how to secure vehicle‐to‐vehicle communication in VANETs has been well studied in recent years .…”
Section: Introductionmentioning
confidence: 99%